PENERAPAN MODEL PEMBELAJARAN GIVING QUESTION AND GETTING ANSWER TERHADAP PENINGKATAN PEMAHAMAN KONSEP MAHASISWA PADA PERKULIAHAN PERKEMBANGAN PESERTA DIDIK - Palestina, Siti Maryam Fadhilah; ., Samingan; Apriana, Evi (Universitas Almuslim, 2015)
This study were aimed to know : different concept understanding students who taught using Giving Question and Getting Answer with students who taught using conventional learning The sample in this study were two classes is determined by cluster random sampling, consist of an exsperimental class(Giving Question and Getting Answer) and the control class (conventional). The technique of analyzing data was conducted through t test. The conclusion of the research is a significant different concept understanding students who taught using Giving Question and Getting Answer with students who taught using conventional learning. Key words: concept understanding, Giving Question and Getting Answer